Development of An Integrated Assessment Instrument to Measure Students’ Critical Thinking and Chemical Literacy Skills for Rate of Reaction Topic - Nurlaila Widyanarti Ariefiani; Endang Widjajanti Laksono (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking is one of the 21st-century skills needed. Understanding chemical literacy can encourage students to be able to think more critically. Given the importance of critical thinking and chemical literacy in chemistry learning, there is a need for an assessment instrument that can measure both abilities. Based on this, the integrated assessment instrument was developed to determine the characteristics and feasibility of the integrated assessment instrument that can measure students' critical thinking skills and chemical literacy on reaction rate materials. The sample in this study is 154 students from two high schools in Makassar City. The feasibility and characteristics of the integrated assessment instrument were analyzed using the Rasch model with the Partial Credit Model-1 Logistic Parameter (PCM-1PL) approach. The results of the analysis show that the 10 items developed are valid and have a high reliability value. The integrated assessment instrument has the characteristics of fit with the model, and the difficulty level of the items is classified as good. The results of this study show that the integrated assessment instrument can be used as a good instrument to measure students' critical thinking skills and chemical literacy on reaction rate materials